The Aspirations of New Technology-Based Firms in CEE and CIS Countries - Przemyslaw Zbierowski (Foresight and STI Governance)
The main purpose of this paper is to assess the possible impact of new technology-based firms on the social and economic development of Central and Eastern European (CEE) and Commonwealth of Independent States (CIS) countries by analyzing the share of such firms among entrepreneurs and society and by investigating data on their expected growth, innovativeness, and internationalization. The study contributes to forecasting the future effects caused by NTBFs on the economy of CEE and CIS countries. We use pooled samples from 2013–2015 from the Global Entrepreneurship Monitor for: Russia (pooled sample size: 4,030), Hungary (6,003), Romania (6,024), Poland (6,001), Lithuania (4,000), Latvia (4,004), Estonia (6,662), Czech Republic (5,009), Slovakia (6,010), and Kazakhstan (4,205). Most analyses are based on a one-way ANOVA analysis of the differences of in the average size of country indicators for the analyzed countries. The research results point to significant differences among the analyzed countries. The share of NTBF owners ranges from 0.7% (Russia) to almost 5% (Slovakia, Romania, and Kazakhstan). NTBFs also substantially differ across countries in terms of projected growth (highest in Hungary and lowest in Russia), internationalization (highest in Latvia, lowest in Russia) and innovativeness (highest in Poland, lowest in Kazakhstan). The main limitations of this study are as follows. The sample used was not chosen specifically for the task. Moreover, the assessment of the novelty of the technology is based on entrepreneur’s self-assessment, so we might expect a bias in that regard. The data on projected growth, internationalization and innovations are just the expectations of the entrepreneurs themselves, so again, bias is expected. The relationships presented in the paper might be strongly influenced by external factors and sample pooling might even magnify that impact. The paper has implications for the policies developed to support entrepreneurship in order to facilitate growth, internationalization, and innovativeness at NTBFs.